2009
DOI: 10.1179/crn.2009.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low Intensity Laser Therapy In Myofascial Pain Syndrome

Abstract: Limited studies have demonstrated that low intensity laser therapy (LILT) may have a therapeutic effect on the treatment of myofascial pain syndrome (MPS). Sixty (60) patients with MPS and having one active trigger point in the anterior masseter and anterior temporal muscles were selected and assigned randomly to six groups (n=10): Groups I to Ill were treated with GaAIAS (780 nm) laser, applied in continuous mode and in a meticulous way, twice a week, for four weeks. Energy was set to 25 J/cm2, 60 J/cm2 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 19 publications
3
63
0
1
Order By: Relevance
“…10 Carrasco et al also reported that LLLT was effective in pain reduction of patients with MPS. 11 In regard to improvements in quality of life, in our study we observed that patients treated with IVL and PLLL had more significant (P < 0.0001) improvement in quality of their lives compared to the control group as well as when compared to before treatment. Here again, there was no statistical difference (P = 0.9) in improvement of quality of life between the IVL group and the PLLL group, despite a better quality of life in the IVL group when compared to the PLLL group.…”
Section: Discussionsupporting
confidence: 52%
“…10 Carrasco et al also reported that LLLT was effective in pain reduction of patients with MPS. 11 In regard to improvements in quality of life, in our study we observed that patients treated with IVL and PLLL had more significant (P < 0.0001) improvement in quality of their lives compared to the control group as well as when compared to before treatment. Here again, there was no statistical difference (P = 0.9) in improvement of quality of life between the IVL group and the PLLL group, despite a better quality of life in the IVL group when compared to the PLLL group.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, we used 6.36 J/cm 2 energy density. Carrasco et al 29 used very high energy densities (25, 60, 105 J/cm 2 ). Since they did not obtain favorable results and based on the suggested energy density values for GaAsAl laser, 30 we used a lower energy density.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the stability of the results of laser therapy, VAS has been used in previous studies. Carrasco et al 29 assessed the level of pain of patients using a VAS 15 days and 1 month following completion of treatment. Dundar et al 25 used VAS 4 weeks after initiation of treatment and Altan et al 26 used VAS at 0, 2, 12 and 14 weeks following treatment to assess the pain severity in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight other RCTs also showed the pain-relieving effect of LA; some of these focused on myofascial pain over the cervical region [16,17], masseter [18], masticatory muscles [19,20], trapezius [21,22], or trigger points [23]. The consistency of these trials highlighted the efficacy of LA in the treatment of myofascial pain.…”
Section: Myofascial Painmentioning
confidence: 99%